Mask-free patterning of Cu mesh as smart windows by spatially modulated nanosecond laser pulses. (August 2021) - Zhang, Qingwei; Huang, Donglin; Qi, Dongfeng; Zhou, Wenju; Wang, Letian; Zhang, Zifeng; Chen, Songyan; Dai, Shixun; Zheng, Hongyu
Highlights: Low-cost copper mesh by a maskless nanosecond laser direct ablation process. The square shaped mesh without outward radial mass on the edge of metallic meshes. The copper mesh presents an excellent a filtration in Vis and NIR regions. The copper mesh was demonstrated enhanced thermal shielding efficiency. Abstract: Laser direct fabrication of metallic mesh is a very promising structure for the next-generation transparent electrodes due to its outstanding optical and electrical properties. However, photoelectric properties and morphologies of the metallic mesh electrodes are not excellent after Gaussian pulse laser writing technology, which largely restricts the development of laser direct ablation process for the fabrication of high-quality transparent electrodes. In this study, we present newly developed copper mesh transparent electrode by spatially modulated one-step top-flat square nanosecond laser direct writing ablation of Cu film under ambient conditions. The copper square shaped electrode without outward radial mass transfer of molten metal, and no structural deformation and damage on the edge of metallic meshes. The clean square shaped of copper meshes structure not only shows high optical transparency in visual region and excellent a filtration in NIR regions, but also presents electrothermogenic of conductive copper mesh. In addition, the clean square shaped of copper mesh electrode on glass was demonstrated enhanced thermal shielding efficiency and defrost test as the smart windows.